Risiko Kanker Payudara pada Pengguna Obat-obatan Hormonal - PURWANTO, DENNI JOKO; REUWPASSA, JAUHARI OKA; ADISASMITA, ASRI C (Indonesian Journal of Cancer, 2014)
Commonly hormonal drugs used by woman are contraceptive and hormone replacement therapy (HRT). A contraceptive user in Indonesia is about 62% aged 16-49 years, modern contraceptive users is 58%. Injected contraception user is 32% followed by oral contraceptive (pill) is 14%. Literature review conducted in this study. The risk use of both hormonal contraception and HRT causing breast cancer still have different opinion The researchers concluded that both of these factors affect the incidence of breast cancer.